Isolation and Identification of Endophytic Bacteria from Euphorbia hirta L. (Patikan Kebo) - Rindiyani Rindiyani; Ratu Intan Anugrah; Bella Nabila; Sisilia Salsabilla; Elia Susanti; Desi Rofiani; Yolanda Puspytha; Risky Hadi Wibowo; Sipriyadi Sipriyadi; Welly Darwis (Universitas Labuhanbatu, 2025)
Patikan Kebo (Euphorbia hirta L.) is a plant that lives scattered in the yard, has potential as an antibacterial, one way to extract plants is by isolating endophytic bacteria. Endophytes are bacteria found in plant tissue. The purpose of this study was to isolate and identify the morphology of endophytic bacteria from plant Patikan Kebo (Euphorbia hirta L.). The method used is the Total Plate Count (TPC) method by taking samples, isolating bacteria, pure culture, morphological identification, and Gram staining. Endophytic bacteria were obtained by isolating parts of the plant Patikan Kebo (E. hirta L.), namely the roots of patikan kebo (PRE), Patikan kebo stem endophyte (PSE) and Patikan kebo leaves endophyte (PLE). The results of the study found 22 isolates, endophytic bacterial isolates have diverse morphological characteristics including appearance, elevation, edges and color. There are 20 isolates of endophytic bacteria that belong to the Gram positive group and 2 isolates of endophytic bacteria that belong to the Gram negative group. It can be concluded that endophytic bacterial isolates from Patikan Kebo (Euphorbia hirta L.) plants have different morphologies